Appropriate Nitrogen Schedules in Direct Seeded Rice (Oryza sativa L.) - Kaur, Jagmohan; Kaur, Jagroop (International Journal of Bio-resource and Stress Management, 2017)
Nitrogen being a key nutrient in promoting the plant growth, plays an important role in determining the yield potential of rice. But in case of rice, recovery of applied nitrogen is very low on account of various losses viz., ammonia volatilization, denitrification, run off and leaching. Moreover, transplanted rice is being replaced by aerobic rice culture for saving water, labour as well as energy. In contrary to flooded conditions, the dominant form of nitrogen is nitrate under aerobic conditions and further alternate wet and dry conditions stimulate nitrification and denitrification processes which increase N losses and relatively low N uptake by DSR makes nitrogen management even more dynamic. Application of nitrogen at the stages which coincide with the period of efficient utilization, is of immense importance to meet the nitrogen requirement of direct seeded rice (DSR) throughout the growing season. Thus, improvement in N management can be done by adopting those strategies which are based on the requirement as well as temporal variation in crop N demand. This paper reviews the information regarding influence of various nitrogen application schedules on various aspects like yield and quality of DSR. In DSR, those N schedules should be prefered which avoid basal N application to the crop as it remain unutilized by the crop and is lost and also encourages weed growth.